2019
DOI: 10.1111/febs.14827
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in ocular diseases: new and potential therapeutic targets

Abstract: Long non‐coding RNAs (lncRNAs) are non‐protein coding transcripts containing more than 200 nucleotides. In the past, lncRNAs were considered as ‘transcript noise’ or ‘pseudogenes’ and were thus ignored. However, in recent years, lncRNAs have been proven to regulate gene expression at the epigenetic, transcriptional and translational level, and thereby influence cell proliferation, apoptosis, viability, immune response and oxidative stress. Furthermore, increasing evidence points to their involvement in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 79 publications
0
47
0
Order By: Relevance
“…The aberrantly expressed lncRNAs, which act as diagnostic markers, prognostic indicators or predictors of therapeutic response, have been reported in various types of cancer including HCC 23 , 24 . For instance, the identification of tumor-specific transcripts (TSTs), which contain many noncoding RNAs and are detectable in extracellular vesicles from HCC patients' blood, may provide new insights into the development of HCC diagnosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrantly expressed lncRNAs, which act as diagnostic markers, prognostic indicators or predictors of therapeutic response, have been reported in various types of cancer including HCC 23 , 24 . For instance, the identification of tumor-specific transcripts (TSTs), which contain many noncoding RNAs and are detectable in extracellular vesicles from HCC patients' blood, may provide new insights into the development of HCC diagnosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-194 overexpression can also suppress RPE cell EMT by attenuating the expression of Zeb1 ( Cui et al, 2019 ). In addition to miRNAs, long non-coding RNAs (lncRNAs) contribute to the regulation of RPE EMT ( Zhang et al, 2019 ). In RPE cells treated with PVR vitreous or TGF-β1, MALAT1 expression is increased, and knockdown of MALAT1 attenuates the phosphorylation of SMAD2/3 and the expression of Snail, Slug, and Zeb1, preventing cell migration and proliferation ( Yang et al, 2016 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…5,6 Numerous studies have demonstrated that lncRNAs play a vital role in different cellular processes, such as proliferation, differ-entiation, migration, invasion, and apoptosis, and exhibit differential expression in the pathogenesis of ophthalmologic disorders. 5,[7][8][9][10][11][12] Interestingly, some studies have suggested that the lncRNA-mRNA competitive endogenous RNA network plays a role in the transcriptional regulation of I/R injury, in which lncRNA functions as a competitive endogenous RNA (ceRNA) that competes for microRNA (miRNA) in order to increase the expression of a particular target gene. [13][14][15][16] Therefore, we hypothesized whether lncR-NAs could influence the process of apoptosis in RGCs via the ceRNA pathway in a mouse model of I/R damage.…”
mentioning
confidence: 99%